Legal and Economic Perspectives to Sustainable Sovereign Debt Management in Nigeria: Energy Poverty in Perspective - Olika, Daniel (Journal of Sustainable Development Law and Policy, 2025)
In recent times, Nigeria’s total debt stock and its debt management strategies have been a thorny fiscal policy issue in the academia and the media. This is made worse by the fact that the debt profile continues to increase with no infrastructure to show for the increasing debt profile. With contrasting views being canvassed in different circles as to the economic impact of these loans, it has been difficult to state what the exact impact Nigeria’s debt stock has on its economy and how effective the debt management strategies put in place have been. The debates notwithstanding, the fall in oil prices and the impact of the novel corona virus pandemic on the economy leaves the government with extraordinarily little options to address its budget deficit. Despite the dire economic situation, the energy poverty level in the country continues to rise; thereby increasing the need to deploy resources to address energy access in Nigeria. This article therefore undertakes a legal and economic analysis of Nigeria’s debt profile and the debt management strategies. The article does so by comprehensively analysing the economic implications of Nigeria’s debt profile, the impact of its debt management strategies on its economy, and a legal analysis of its debt management strategies and policies. The article also analyses the impact of the total debt stock and the sovereign debt management strategies on energy poverty in the country. The article concludes by arguing that although available data suggests that Nigeria’s public debt is sustainably managed given the low debt to GDP ratio, the high cost of servicing these debts have adverse economic implications on development generally (and energy poverty in particular) and necessitates a thorough review of its legal and policy foundations for managing sovereign debt.